Synthesis of Short Oligonucleotides on a Soluble Support by the Phosphoramidite Method - Gimenez Molina, Alejandro (fi=Turun yliopisto|en=University of Turku|, 2015)
In the last decades, the chemical synthesis of short oligonucleotides has become an important aspect of study due to the discovery of new functions for nucleic acids such as antisense oligonucleotides (ASOs), aptamers, DNAzymes, microRNA (miRNA) and small interfering RNA (siRNA). The applications in modern therapies and fundamental medicine on the treatment of different cancer diseases, viral infections and genetic disorders has established the necessity to develop scalable methods for their cheaper and easier industrial manufacture. While small scale solid-phase oligonucleotide synthesis is the method of choice in the field, various challenges still remain associated with the production of short DNA and RNA-oligomers in very large quantities. On the other hand, solution phase synthesis of oligonucleotides offers a more predictable scaling-up of the synthesis and is amenable to standard industrial manufacture techniques. In the present thesis, various protocols for the synthesis of short DNA and RNA oligomers have been studied on a peracetylated and methylated β-cyclodextrin, and also on a pentaerythritol-derived support. On using the peracetylated and methylated β-cyclodextrin soluble supports, the coupling cycle was simplified by replacement of the typical 5′-O-(4,4′-dimethoxytrityl) protecting group with an acid-labile acetal-protected 5′-O-(1-methoxy-1-methylethyl) group, which upon acid-catalyzed methanolysis released easily removable volatile products. For this reason monomeric building blocks 5′-O-(1-methoxy-1-methylethyl) 3′-(2-cyano-ethyl-N,N-diisopropylphosphoramidite) were synthesized. Alternatively, on using the precipitative pentaerythritol support, novel 2´-O-(2-cyanoethyl)-5´-O-(1-methoxy-1-methylethyl) protected phosphoramidite building blocks for RNA synthesis have been prepared and their applicability by the synthesis of a pentamer was demonstrated. Similarly, a method for the preparation of short RNAs from commercially available 5´-O-(4,4´-dimethoxytrityl)-2´-O-(tert-butyldimethyl-silyl)ribonucleoside 3´-(2-cyanoethyl-N,N-diisopropylphosphoramidite) building blocks has been developed